El Rap Colombiano como Mecanismo para Incentivar el Desarrollo de Conciencia Social a través del Diseño de una Página Web (2024)
In this didactic material there is an approach to social conscience as a soft skill that focuses the human being in thinking about the other from solidarity, leading to generate actions that transform the space that he/she inhabits in order to improve it. Based on the above, it is a skill that must be strengthened in educational training, being the students the new citizens who will be present in society, where the teacher's duty is to enable the construction of integral human beings who are not submerged in the daily life of oblivion but on the contrary, ensure the welfare of others